The effect of referral for genetic counseling on genetic testing and surgical prevention in women at high risk for ovarian cancer: Results from a randomized controlled trial. Issue 22 (22nd July 2016) - Drescher, Charles W.; Beatty, J. David; Resta, Robert; Andersen, M. Robyn; Watabayashi, Kate; Thorpe, Jason; Hawley, Sarah; Purkey, Hannah; Chubak, Jessica; Hanson, Nancy; Buist, Diana S. M.; Urban, Nicole
Abstract : BACKGROUND: Guidelines recommend genetic counseling and testing for women who have a pedigree suggestive of an inherited susceptibility for ovarian cancer. The authors evaluated the effect of referral to genetic counseling on genetic testing and prophylactic oophorectomy in a randomized controlled trial. METHODS: Data from an electronic mammography reporting system identified 12, 919 women with a pedigree that included breast cancer, of whom 625 were identified who had a high risk for inherited susceptibility to ovarian cancer using a risk‐assessment questionnaire. Of these, 458 women provided informed consent and were randomized 1:1 to intervention consisting of a genetic counseling referral (n = 228) or standard clinical care (n = 230). RESULTS: Participants were predominantly aged 45 to 65 years, and 30% and 20% reported a personal history of breast cancer or a family history of ovarian cancer, respectively. Eighty‐five percent of women in the intervention group participated in a genetic counseling session. Genetic testing was reported by 74 (33%) and 20 (9%) women in the intervention and control arms ( P < .005), respectively. Five women in the intervention arm and 2 in the control arm were identified as germline mutation carriers. Ten women in the intervention arm and 3 in the control arm underwent prophylactic bilateral salpingo‐oophorectomy ( P < .05). CONCLUSIONS: Routine referral of women at high risk for ovarian cancer to genetic counseling promotes genetic testing and prophylactic surgery. The findings from the current randomized controlled trial demonstrate the value of implementing strategies that target women at high risk for ovarian cancer to ensure they are offered access to recommended care.CA Cancer J Clin 2016 . ©2016 American Cancer Society, Inc . Cancer 2016;122:3509–3518 . © 2016 American Cancer Society Abstract : Results from a randomized controlled trial confirm that routine referral of women who are at high risk for ovarian cancer to genetic counseling promotes genetic testing and risk‐reduction surgery. These findings motivate action to design and implement efficient strategies to ensure that high‐risk women are identified and offered access to currently available and recommended care.